horsewoman27
New member
- Joined
- Feb 13, 2011
- Messages
- 11
Solve for x.
log3(x+7)=2-log3(x-1)
Write the exact answer using base-10 logarithms.
log3(x+7)=2-log3(x-1)
log3(x+7) + log3(x-1) = 2
log3 [(x+7)/(x-1)] = 2
(x+7)(x-1) = 3^2
x^2 + 6x - 7 = 9
x^2 + 6x - 16 = 0
(x+8)(x-2) = 0
x = -8 or x = 2
but x=-8 would make log3(x+7) undefined, so
x = 2
( why would it ask to use base 10 logs ????)
log3(x+7)=2-log3(x-1)
Write the exact answer using base-10 logarithms.
log3(x+7)=2-log3(x-1)
log3(x+7) + log3(x-1) = 2
log3 [(x+7)/(x-1)] = 2
(x+7)(x-1) = 3^2
x^2 + 6x - 7 = 9
x^2 + 6x - 16 = 0
(x+8)(x-2) = 0
x = -8 or x = 2
but x=-8 would make log3(x+7) undefined, so
x = 2
( why would it ask to use base 10 logs ????)